The Bourdieu paradigm : The origins and evolution of an intellectual social project - Robbins, Derek (Book collections on Project MUSE., 2019)
Analysing the work of Schutz, Gurwitsch, Merleau-Ponty and Bourdieu, this book considers the historical development of competing philosophies of social science. It examines the relations between phenomenology, Gestalt psychology and empirical social science in the first half of the twentieth century and then explores the way in which Bourdieu responded to this legacy by advocating a form of reflexive social-scientific investigation, which would remain faithful to primary experience without disowning accumulated intellectualism. The book asks whether the Bourdieu 'paradigm' retains value beyond the French conditions of its production. It offers an analysis of the development of Bourdieu's thought and practice which constitutes an invitation to readers generally to reassess the value of the western tradition of the social function of the detached intellectual for mass democratic societies. --From publisher's website.